INTERVENSI PSIKOLOGIS TERHADAP PESERTA DIDIK DENGAN MOTIVASI BELAJAR RENDAH - Imam Hanafi (Jurnal Genta Mulia, 2017)
The aim of this research is to look at the various problems faced by students where the problem is not only seen from the individual aspect but from the various sides of the owner close relationship with learning. This research is a type of qualitative research with methods observation, interviews, and documentation. The results of this research show that it is low A student's individual learning motivation is not the only aspect that causes him to have low learning motivation. However, there are several other factors that also influence it. So it's done Psychological intervention with a Person Centered Therapy approach. It is hoped that this approach will able to restore high learning motivation in students